2022
DOI: 10.3390/molecules27061984
|View full text |Cite
|
Sign up to set email alerts
|

Positive Effect of α-Asaronol on the Incidence of Post-Stroke Epilepsy for Rat with Cerebral Ischemia-Reperfusion Injury

Abstract: In the present study, we confirmed that α-asaronol, which is a product of the active metabolites of alpha Asarone, did not affect n-butylphthalide efficacy when n-butylphthalide and α-asaronol were co-administered to rats with cerebral ischemia-reperfusion injury. Our research revealed that the co-administration of α-asaronol and n-butylphthalide could further improve neurological function, reduce brain infarct volume, increase the number of Nissl bodies, and decrease the ratios of apoptotic cells and the expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…These processes are also implicated in neurodegenerative diseases of the CNS such as AD, PD, and others. There is a wealth of evidence suggesting that cerebral ischemia is associated with the development and progression of CNS diseases including ischemic stroke [2], AD [3], PD [4], epilepsy [5], and other [6] related conditions collectively referred to as ischemia-associated CNS diseases [7].…”
Section: Introductionmentioning
confidence: 99%
“…These processes are also implicated in neurodegenerative diseases of the CNS such as AD, PD, and others. There is a wealth of evidence suggesting that cerebral ischemia is associated with the development and progression of CNS diseases including ischemic stroke [2], AD [3], PD [4], epilepsy [5], and other [6] related conditions collectively referred to as ischemia-associated CNS diseases [7].…”
Section: Introductionmentioning
confidence: 99%
“…In our series of studies over the last decade on α-asaronol (( E )-3′-hydroxyasarone), it has been demonstrated to exhibit promising pharmaceutical effects including anticonvulsant and antiepileptic activities with lower biotoxicity compared to the two current common antiseizure drugs of α-asarone and carbamazepine. The in vitro evaluation of α-asaronol on cell viability and neuroprotective activity also revealed a potential protective effect on neuronal oxidative stress . At the same time, further research was conducted on the molecular mechanisms underlying the antiepileptic effects of α-asaronol.…”
Section: Introductionmentioning
confidence: 99%